Особенности формирования образа чрезвычайной ситуации у специалистов по ее ликвидации - Kremen’ Маркс; Gerasimchik Александр; Bogomaz Ольга (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
Characteristics of compiling and functioning of an emergency image in rescuers’ consciousness as a peculiar image of the dynamic object are considered in the article. The structure of rescuers’ activity in the process of emergency elimination is discussed as well. The engineering-psychological plan of actions of an emergency manager is presented, which describes the process of emergency elimination in terms of human engineering.